2013
DOI: 10.1371/journal.pone.0068556
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Small Airway Obstruction among Chinese Island Residents: A Case-Control Study

Abstract: BackgroundWe investigated the prevalence of and risk factors for small airway obstruction (SAO) among Chinese island residents to establish means to prevent and treat SAO.MethodsFrom October 17, 2011 to November 1, 2011, a total of 2,873 residents aged >20 years who lived on the Huangqi Peninsula of Fujian were recruited by random cluster sampling. They were asked to complete a Burden of Obstructive Lung Disease (BOLD) questionnaire and underwent physical examinations and lung function evaluations. SAO was def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(27 citation statements)
references
References 28 publications
0
26
1
Order By: Relevance
“…Three studies used FEF 25–75 /FVC [ 35 – 37 ]. Two studies used FEF 25 , FEF 50 or FEF 75 either alone [ 38 ] or in combination [ 39 ]. One study used FEV 3 /FVC [ 40 ] and another used both FEV 3 /FVC and FEV 3 /FEV 6 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three studies used FEF 25–75 /FVC [ 35 – 37 ]. Two studies used FEF 25 , FEF 50 or FEF 75 either alone [ 38 ] or in combination [ 39 ]. One study used FEV 3 /FVC [ 40 ] and another used both FEV 3 /FVC and FEV 3 /FEV 6 .…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies presented criteria defining an abnormal result (Table 1 ), utilising eight separate methods. Three used percent predicted cut offs including: FEF 25–75 < 75% [ 29 ], FEF 25–75 < 67% [ 23 ], and FEF 50 < 70% predicted [ 38 ]. Two used LLN for FEV 3 /FVC [ 12 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Low maximal midexpiratory flow rate is an indicator of small airway obstruction. We have not studied the relationship between MS and its components and this marker for small airway obstruction, but in a previous study, we have reported that diabetes mellitus, high WC, smoking and exposure to second‐hand smoke increase the risk of small airway obstruction, and regular exercise decreases this risk.…”
Section: Discussionmentioning
confidence: 99%